2011
DOI: 10.1038/nature10336
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of recombination in African Americans

Abstract: Recombination, together with mutation, is the ultimate source of genetic variation in populations. We leverage the recent mixture of people of African and European ancestry in the Americas to build a genetic map measuring the probability of crossing-over at each position in the genome, based on about 2.1 million crossovers in 30,000 unrelated African Americans. At intervals of more than three megabases it is nearly identical to a map built in Europeans. At finer scales it differs significantly, and we identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
380
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(394 citation statements)
references
References 29 publications
12
380
2
Order By: Relevance
“…And individuals who carry the motif tend to have a higher risk of the disease-causing genomic rearrangements. Wegmann et al [30] showed that recombination rates at regions with known large chromosomal structural variants, especially inversions, are likely to be highly population specific compared with those at other regions.…”
Section: Estimating Recombination Rates Based On Population Genetic Mmentioning
confidence: 99%
See 1 more Smart Citation
“…And individuals who carry the motif tend to have a higher risk of the disease-causing genomic rearrangements. Wegmann et al [30] showed that recombination rates at regions with known large chromosomal structural variants, especially inversions, are likely to be highly population specific compared with those at other regions.…”
Section: Estimating Recombination Rates Based On Population Genetic Mmentioning
confidence: 99%
“…Based on the observed ancestry switch points in admixed population, Hinch et al [29] and Wegmann et al [30] constructed a high-resolution recombination map of African American in 2000, respectively. It was novel to use ancestry-based approach to identify recombination events and recombination hotspots.…”
Section: Estimating Recombination Rates Based On Population Genetic Mmentioning
confidence: 99%
“…A miscopy rate parameter is used to account for the differences between "real" and "copied" ancestry. In HAPMIX, an EM algorithm is used to estimate those parameters for African Americans [109].…”
Section: Incomplete Lineage Sortingmentioning
confidence: 99%
“…However, the study presented here remains relatively small when one looks at the individual disease groups (200 + for each of refl ux cases, Barrett ' s and EAC). Specifi cally, the variation of genetic material between worldwide human populations is 0.1 % of the genome ( 14 ). Since BE is more common in white males especially in Caucasians, the need for well-characterized ethnic and gender controls such as provided here is vital to avoid potentially spurious diff erences as could be present here.…”
mentioning
confidence: 99%